USE OF DRUGS DURING THE FIRST TRIMESTER OF PREGNANCY IN TERMS OF FOETUS SAFETY: ANALYSIS OF PRESCRIBINGS - A. P. Pereverzev; A. N. Mironov; N. D. Bunyatyan; V. K. Lepakhin; B. K. Romanov (Безопасность и риск фармакотерапии, 2022)
The article presents the results of analysis of the use of drugs in the first trimester of pregnancy from the point of view of safety to the fetus